PENGARUH FAKTOR MAKROEKONOMI TERHADAP TOTAL NILAI EMISI SUKUK KORPORASI DI INDONESIA (PERIODE JANUARI 2013-DESEMBER 2017) - Mohamad Arif Wahyudi; Atina Shofawati (Universitas Airlangga, 2019)
This research aims to analyze the influence of inflation, rupiah exchange rate and SBIS reward to total value of corpotate sukuk emissions in Indonesia. all data uses in this research contained from Bank Indonesia, Kemendag Indonesia and Otoritas Jasa Keuangan . This research used the quantitative approach method. The data analysis method used in this research is multiple linier regression analysis. Based on the result of this research showed that simultaneously inflation, rupiah exchange rate and SBIS reward had significant effect to total value of corporate sukuk emissions with significant value 0,000. Partial test are showed that inflation and SBIS reward has significant and negative affect to total value of corporate sukuk emissions, while rupiah exchange rate has significant and positive affect to total value of corporate sukuk emissions in Indonesia period January 2013 to Desember 2017.Keywords: Corporate Sukuk, Inflation, Rupiah Exchange Rate, Certificate of Sharia Indonesian Bank (SBIS)REFERENCESAnshori, Muslich dan Sri Iswati. 2009. Buku Ajar Metodologi Penelitian Kuantitatif.Surabaya: Pusat Penerbitan danPercetakan Unair (AUP).Ardiansyah, IH dan Lubis D. 2017. The effect of Macroeconomic Varibles to CorporateSukuk Growth in Indonesia. Jurnal AlMuzara’ah, Vol. 5 No.1, 2017(ISSN p:23376333; e: 2355-4363).Bakri, Syaiful. 2004. Analisis Faktor-Faktor yang Mempengaruhi Harga Saham (StudiKasus Perusahaan Terdaftar di JII). Tesis.Jakarta: Pasca Sarjana PIKTI-UI.Dewan Syariah Nasional. 2003. Fatwa DSN MUI Nom: 40/DSN-MUI/X/2003 TentangPasar Modal dan Pedoman UmumPenerapan Prinsip Syariah di Bidang Pasar Modal. (online) www.dsnmui.or.id. diaksespada 25 Maret 2018.Hidayat, Taufik. 2011. Buku Pintar Investasi Syariah. Jakarta: Mediakita.Karim, Adiwarman A. 2007. Ekonomi Makro Islam, Edisi kedua. Jakarta: PT RajaGrafindo Persada.______________. 2008. Ekonomi Makro Islam. Jakarta: PT Raja Grafindo Persada.Kholis, Nur. 2010. Sukuk: Instrumen Investasi yang Halal dan Menjanjikan. La_Riba Jurnal Ekonomi Islam, Vol. IV No. 2, Desember 2010Manab, Abdul dan Sujianto Agus Eko. 2016. Pengaruh Stabilitas Ekonomi Makro Terhadap Penerbitan Sukuk Negara di Indonesia, Malaysia dan Brunai Darussalam. Tulungagung: Cahaya Abadi. Manan, Abdul. 2010. Aspek Hukum dalam Penyelenggaraan Investasi di Pasar Modal Syariah Indonesia. Jakarta: KENCANA.Mankiw, N. Gregory. 2007. Makroekonomi, Edisi keenam. Jakarta: Erlangga.Putong, Iskandar. 2003. Pengantar: Ekonomi Mikro & Makro, Edisi kedua. Jakarta: Ghalia Indonesia.Rini, Mustika. 2012. Obligasi Syariah (Sukuk) dan Indikator Makroekonomi Indonesia:Sebuah Analisis Vector Error CorrectionModel (VECM). Skripsi. Bogor: Institut Pertanian Bogor.Rodoni dan Herni Ali, Ahmad. 2010. Manajemen Keuangan, Edisi 1. Jakarta:Wacana Media.Ryandono, Muhamad Nafik H. 2009. Bursa Efek dan Investasi Syariah. Jakarta: Serambi Ilmu Semesta.Santoso, Singgih. 2000. Buku Latihan SPSS: Statistik Parametrik. Elex Media Komputindo.Sugiyono. 2011. Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung:ALFABETA.Sujarweni, V. Wiratma. 2014. SPSS untuk Penelitian. Yogyakarta: Pustaka Baru Press.Wahid, Nazzarudin Abdul. 2010. Sukuk: Memahami dan Membedah Obligasipada Perbankan Syariah.Yogyakarta: Kanisius.http://www.bi.go.id/id/moneter/inflasi/data/Default.aspx (Diakses Pada oktober 2017)https://www.bi.go.id/id/moneter/operasi/lelang-sbi/Pages/SBIS_15122017.aspx (Diakses Pada Oktober 2017)http://www.kemendag.go.id/id/economic-profile/economic-indicators/exchange-rates (Diakses Pada Oktober 2017)https://www.ojk.go.id/id/kanal/syariah/data-dan-statistik/data-produk-obligasi-syariah/Default.aspx (Diakses Pada Oktober 2017).